Pengaruh Persepsi Khalayak Remaja Tentang Vlog-Vlog Atta Halilintar dan Intensitas Komunikasi Peer Group Remaja Terhadap Tingkat Motivasi Remaja Menjadi Subscriber Atta Halilintar - Iga Tikah Rilanti; Sunarto ,. (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This study aims to explain the effect of youth audience perceptions about Atta Halilintar’s vlogs and youth peer group communication intensity towards the youth motivation level becoming Atta Halilintar’s substriber. Explained by the Theory of Uses and Gratifications, through an integrative model by one of the communication scientists Philip Palmgreen. Sampling in this study was conducted using probability sampling and multistage random sampling techniques. The population in this study were all high school students in the city of Semarang on the condition that they had watched the Atta Halilintar vlog show. Data analysis was performed using multiple linear regression analysis. If influenced by these two variables, namely youth audience perceptions about Atta Halilintar’s vlogs and youth peer group communication intensity together, then there is a positive influence with a strong closeness towards youth audiences motivation level to become Atta Halilintar’s subscriber. However, if the two variables are tested partially it shows other results. Where the results of the study show that youth audience perceptions about Atta Halilintar’s vlogs have a positive influence on youth audiences motivation level to become Atta Halilintar’s subscriber, while youth peer group communication intensity does not show any influence on youth audiences motivation 2 level to become Atta Halilintar’s subscriber. When influenced by the two variables together, youth audience perceptions about Atta Halilintar’s vlogs is more dominant than youth peer group communication intensity.